DEVELOPING THE MOTIVATION OF PUPILS TO LEARN WITH ICT MEANS - Kozyr, Margarita (Educological discourse, 2020)
The article analyzes the latest research on the development of students' motivation to learn through ICT; defined the concept of "information and communication technologies" as the basis of quality educational process in the development of the information society; an attempt is made to characterize the pedagogical tasks of information and communication learning based on the study of the components of the motivational sphere of the modern generation and to describe the methodology and technology of the educational process using the latest electronic learning tools primarily computers. For the purpose of integration of modern information and communication technologies in training preparation of pupils for full life in the conditions of information society, and also formation of motives of training as process of creation in school of conditions for emergence of internal motivations (motives, the purposes, emotions) and their further self-development of their own motivational sphere. It is investigated that modern information technologies in the learning process allow: to intensify the cognitive activity of students; provide positive motivation for learning; to conduct lessons at a high aesthetic and emotional level; to ensure a high degree of differentiation of learning (almost individualization) increase the amount of work performed in the lesson by 1.5-2 times; improve knowledge control; rationally organize the educational process; to increase the efficiency of the lesson, to form skills of search and research activity; provide access to various reference systems, electronic libraries and other information resources. The author concludes on the choice of optimal methods for the development of motivation to learn, taking into account the psychological and pedagogical aspects of this process; the conditions necessary for formation of motivation of pupils to training and maintenance of humane relations between the teacher and the pupil are characterized; Prospects for further research are identified, which consist in studying the specifics of the transformation of educational and cognitive motives into "meaning-making", ie their transition to a new – personal level.